Festive in Death - Robb, J. D., 1950- (New York : Berkley Books, 2015)
Eve Dallas deals with a homicide and the holiday season. Personal trainer Trey Ziegler was in peak physical condition. If you didnt count the kitchen knife in his well-toned chest. Lieutenant Eve Dallas soon discovers a lineup of women whod been loved and left by the narcissistic gym rat. While Dallas sorts through the list of Zieglers enemies, shes also dealing with her Christmas shopping list -- plus the guest list for her and her billionaire husbands upcoming holiday bash. Feeling less than festive, Dallas tries to put aside her distaste for the victim and solve the mystery of his death. There are just a few investigating days left before Christmas, and as New Years 2061 approaches, this homicide cop is resolved to stop a cold-blooded killer.
Keywords: Dallas, Eve -- (Fictitious character) -- Fiction; Policewomen -- New York (State); New York; Fiction; Personal trainers -- Crimes against; Fiction; Detective and mystery fiction